Completion of CVRP with a Combination of Sweep and Local Search Algorithms (Case Study: PT. AJW) - Zakaria Alfikri Sirait; Riri Syafitri Lubis (Numerical: Jurnal Matematika dan Pendidikan Matematika, 2023)
AJW is a consumer goods distribution company for Indofood products and non-Indofood products. PT. AJW moves throughout Karo district. The number of tourist attractions in Karo makes the demand for goods higher such as Pop noodles, Indomie, chitato and others. Thus, having an impact on the distribution of goods Based on the author's observations at PT. AJW Kabanjahe has no standard provisions in determining the route, the delivery of goods is still carried out based on requests from consumers so that it ignores the distance traveled and time. A way that can solve this distribution problem is the Capacitated Vehicle Routing Problem (CVRP). CVRP is a problem in determining the optimal route by looking at the problem that each vehicle has a capacity limit. To solve CVRP problems, a good heuristic algorithm is used is the sweep algorithm and local search route improvement. This study uses the sweep algorithm to solve the CVRP problem, and the routes obtained by the sweep algorithm will be improved with local search. The sweep algorithm is a simple method of calculation, even for calculating large problems. The sweep algorithm will be combined with local search. Local search is an algorithm used to get shorter routes. The combination of the two algorithms is perfect for solving CVRP problems. After research, a distance of 39.96 km was obtained compared to the company's route of 103.5 km. So the percentage of mileage savings is 61.39%. This shows that sweep algorithms can minimize distance while saving company expenses